2015
DOI: 10.52324/001c.8058
|View full text |Cite
|
Sign up to set email alerts
|

Are Industry Clusters and Diversity Strange Bedfellows?

Abstract: In this address, I review industry clustering and diversification strategies to compare and contrast their underlying foundations. The lack of a consensus choice of one or the other for regional economic development strategies along with the recognition that in the dynamic process of development these two processes are related leads me to conclude that clusters and diversity need not be such strange bedfellows after all, and that a rational approach to economic development can leverage the strengths of each an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…De Araújo et al (2019) used data from 558 Brazilian regions for 1995–2015 to demonstrate that industry diversity is negatively related to regional economic development, which is consistent with some research findings in the study of Barufi et al (2016). Interestingly, a few scholars argued that no strategy is superior to the other and that local authorities should leverage each strategy’s strengths and offset weaknesses (Jackson, 2015). Song et al (2021) found that both specialization and diversification affected marine economic growth in 11 Chinese coastal provinces from 2006 to 2014.…”
Section: Literature Reviewsupporting
confidence: 62%
See 1 more Smart Citation
“…De Araújo et al (2019) used data from 558 Brazilian regions for 1995–2015 to demonstrate that industry diversity is negatively related to regional economic development, which is consistent with some research findings in the study of Barufi et al (2016). Interestingly, a few scholars argued that no strategy is superior to the other and that local authorities should leverage each strategy’s strengths and offset weaknesses (Jackson, 2015). Song et al (2021) found that both specialization and diversification affected marine economic growth in 11 Chinese coastal provinces from 2006 to 2014.…”
Section: Literature Reviewsupporting
confidence: 62%
“…Wagner (2000) indicated that "the empirical literature examining the relationship between diversity and growth and stability is inconclusive, in part, due to the variety of diversity measures resulting from inconsistency within the literature on defining diversity" (p. 19). There are several popular diversity measures that have been used in literature: Entropy Index (Kort, 1981;Attaran, 1986;Malizia and Ke, 1993;Trendle and Shorney, 2003), Herfindahl-Hirschman Index (Izraeli and Murphy, 2003;Simonen et al, 2015;Sahu, 2017;Chen, 2019) and Ogive Index (Jackson, 1984(Jackson, , 2015. For these indexes, the notion of perfect diversity in a region is defined as equal shares of economic activity across all industries.…”
Section: Societal Impact Of Industrial Diversitymentioning
confidence: 99%